PEMBANGUNAN DAN PEMELIHARAAN INFRASTRUKTUR TRANSPORTASI DI REGENTSCHAP PEMALANG MASA KOLONIAL BELANDA - Ilham Nur Utomo (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This article aims to uncover the background and dynamics of transportation infrastructure development in the Regentschap Pemalang during the Dutch colonial period. Transportation infrastructure is a vital element supporting community mobility. However, it has often been overlooked in Indonesian historiography, particularly in the context of hinterland regions such as the Regentschap Pemalang. This research employed historical research methods. The findings indicate that transportation infrastructure played a significant role in the social and economic dynamics of the Regentschap Pemalang. Transportation connected Pemalang with other regions, integrating it into the broader transportation network of Java Island. This strategic role underpinned the development and maintenance of transportation infrastructure, particularly land transportation. Roads and railway lines were types of infrastructure that frequently received attention from the colonial government. Nevertheless, such efforts did not always proceed smoothly due to financial constraints and economic disruptions caused by unstable economic conditions.